Artistic Images of Wartime Childhood in the Drawings by Spanish and Soviet Children of the 1930s–1940s - O. V. Khukhrina (Ибероамериканские тетради, 2025)
An artistic image is the basis of any art form. For instance, it can act as a structural unit of a figurative system in children’s drawings of war. In this case, artistic images of wartime childhood in drawings made by children during the Spanish Civil War (1936–1939) and the Great Patriotic War in the Soviet Union (1941–1945) are examined in the historical context of war. The artistic images of drawings by Spanish and Soviet children have a number of similarities in terms of genre, subject and composition; hence, they can be divided into certain typological groups, such as image-event, image-personality, image-copy, and image-idea. Children’s works of the time often depict different events in history, as well as their life in dire circumstances. The drawings of war by Spanish and Soviet children show a similar gamut of wartime childhood images, such as surviving an air raid, paying close attention to one’s surroundings, venerating the country’s leaders, experiencing the consequences of war, glorifying the heroic past and contemplating the cultural heritage. These images are in line with the values of that time and correlate to the ideological and sociocultural processes of different periods. The artistic conceptualization of reality manifests itself in unique genres and thematic compositions. Children’s works are incredibly profound, clear and compelling, while their authors sometimes invent their own drawing techniques. Children tell their personal stories in portraits and drawings on various subjects where fairy-tale images collide with the reality of war, thus creating features of a new genre.